Sirolimus and Autophagy Inhibition in Lymphangioleiomyomatosis: Results of a Phase I Clinical Trial - El-Chemaly, Souheil; Taveira-Dasilva, Angelo; Goldberg, Hilary J; Peters, Elizabeth; Haughey, Mary; Bienfang, Don; Jones, Amanda M; Julien-Williams, Patricia; Cui, Ye; Villalba, Julian A; Bagwe, Shefali; Maurer, Rie; et al. (Chest, 2017)
Animal and cellular studies support the importance of autophagy inhibition in lymphangioleiomyomatosis (LAM). In a cohort of subjects with LAM, we tested the hypothesis that treatment with sirolimus and hydroxychloroquine (an autophagy inhibitor) at two different dose levels is safe and well tolerated. Secondary end points included changes in lung function. This 48-week, two-center phase I trial evaluated the safety of escalating oral hydroxychloroquine doses (100-200 mg) given twice a day in combination with sirolimus to eligible patients ≥ 18 years old with LAM. Subjects received combination therapy for 24 weeks followed by an observation phase without taking study drugs for an additional 24 weeks. Fourteen patients provided written informed consent. Thirteen were treated in cohorts of three patients each with escalating hydroxychloroquine doses (200 and 400 mg) and an extension phase at the 400-mg dose. The most common adverse events were mucositis, headache, and diarrhea. No drug-related serious adverse events were reported. Secondary end points showed improvement in lung function at 24 weeks, with a decrease in lung function at the 48-week time point. When the higher dose of hydroxychloroquine was analyzed separately, FEV and FVC remained stable at 48 weeks, but the 6-min walk distance showed a decrease toward baseline. The combination of sirolimus and hydroxychloroquine is well tolerated, with no dose-limiting adverse events observed at 200 mg twice a day. Potential effects on lung function should be explored in larger trials. ClinicalTrials.gov; No.: NCT01687179; URL: www.clinicaltrials.gov.